Disgusting odours affect the characteristics of the Adaptive Force in contrast to neutral and pleasant odours - Laura V. Schaefer (Nature Portfolio, 2021)
Abstract The olfactomotor system is especially investigated by examining the sniffing in reaction to olfactory stimuli. The motor output of respiratory-independent muscles was seldomly considered regarding possible influences of smells. The Adaptive Force (AF) characterizes the capability of the neuromuscular system to adapt to external forces in a holding manner and was suggested to be more vulnerable to possible interfering stimuli due to the underlying complex control processes. The aim of this pilot study was to measure the effects of olfactory inputs on the AF of the hip and elbow flexors, respectively. The AF of 10 subjects was examined manually by experienced testers while smelling at sniffing sticks with neutral, pleasant or disgusting odours. The reaction force and the limb position were recorded by a handheld device. The results show, inter alia, a significantly lower maximal isometric AF and a significantly higher AF at the onset of oscillations by perceiving disgusting odours compared to pleasant or neutral odours (p < 0.001). The adaptive holding capacity seems to reflect the functionality of the neuromuscular control, which can be impaired by disgusting olfactory inputs. An undisturbed functioning neuromuscular system appears to be characterized by a proper length tension control and by an earlier onset of mutual oscillations during an external force increase. This highlights the strong connection of olfaction and motor control also regarding respiratory-independent muscles.